A new recommendation for febrile urinary tract infection in children aged 2-24 months: Tepecik UTI Guideline-2 - Koyun Cezayir, Begüm; Yavaşcan, Önder; Alaygut, Demet; Kasap Demir, Belde; Mutlubaş, Fatma; Arslansoyu Çamlar, Seçil; Alparslan, Caner; Soyaltın, Eren; Özgür, Su (NLM (Medline), 2023)
AIM: Urinary tract infections (UTIs) represent a common febrile illness in infancy. The study compared two UTI guidelines in terms of number of imaging studies, presence of parenchymal damage and radiation exposure in patients with the first febrile UTI between 2 and 24?months of age. METHOD: The results of Tepecik UTI Guideline-1 used until 2012 (Group 1, n?=?105) were retrospectively compared with Tepecik UTI Guideline-2 (Group 2) used after 2013. In Group 1, urinary tract ultrasonography (US), dimercaptosuccinic acid (DMSA) and voiding cystourethrography (VCUG) were made in all patients. In Group 2, if the US result was abnormal, patients were evaluated with VCUG and DMSA. If the US was normal, only DMSA was performed. If the DMSA was abnormal, the VCUG was undergone (n: 43, 40.9%). RESULTS: The abnormal VCUG detection rate was 69.2% in Group 1 and 30.8% in Group 2 (p?=?0.09). Sensitivity and specificity of US in the diagnosis of vesicoureteral reflux (VUR) was 15.9% and 96.7% in Group 1 and 61.5% and 70.5% in Group 2, respectively. Abnormal DMSA findings were observed among 33.3% (Groups 1) and 66.7% (Groups 2) subjects, respectively (p?>?0.05). The median radiation exposure (500?mrem) of patients in Group 1 was statistically significantly higher than those in Group 2 (200?mrem) (p?<?0.001). CONCLUSION: The VCUG should not be the first examination to be considered in such patients. We think that Tepecik UTI Guideline-2 reduces unnecessary invasive procedure and radiation exposure and not missed VUR in the management of children with UTI at 2-24?months. Needs prospective follow-up studies before considering this recommendation.
Keywords: Febrile Urinary Tract Infection; Infancy; Ultrasonography; VCUG; DMSA Scintigraphy